Musyawarah Program: Analyzing Narasi TV’s Agenda Setting Strategy for the 2024 Presidential and Vice Presidential Election Issue - Fazli, Luthfi; Putri, Kinkin Yuliaty Subarsa (Tecno Scientifica Publishing, 2024)
Indonesia was carrying out the General Election Agenda for the President and Vice President, which was held every five years. 2024 is an election year in which the Indonesian people will choose their leader. Consequently, election coverage dominated program content and news from the mass media, particularly television. Narasi TV had also reported on these electoral issues by airing the Musyawarah show, a special program about the 2024 presidential election. Based on this, the study's goals were to evaluate the role of Narasi TV’s creative team in shaping the media agenda for the 2024 presidential election and to determine what Narasi TV and the creative team anticipate from the public through the Musyawarah program. The research method used in this article was a qualitative research method, specifically the descriptive-qualitative method, focusing on data from literature reviews from various references to analyze how the Narasi TV creative team applies Agenda Setting theory to the issue of the 2024 presidential election through the Musyawarah program. The results showed that Narasi TV’s media agenda on the issue of the 2024 presidential election includes the existence of a special program on the topic, namely the Musyawarah program. Additionally, the creative team’s media agenda for the Musyawarah program includes efforts to raise issues around the 2024 presidential election that are frequently disregarded or neglected by other mass media, despite their significance.